Hindu God, Christian God - Clooney, Francis X. (Oxford University Press, 2001)
This volume offers an in-depth study of key themes common to the Hindu and Christian religious traditions. It redefines how we think about Hinduism, comparative study, and Christian theology. This book offers a bold new look at how traditions encounter one another, and how good comparisons are to be made. Redefining theology as an interreligious, comparative, dialogical, and confessional practice open to all people, it invites not only Hindus and Christians, but also theologians from all religious traditions, to enter into conversation with one another